Peran Pemerintah dalam Penyelesaian Konflik Penambangan Bahan Galian C melalui Proses Mediasi ( Kasus Konflik Penambangan antara PT BRD Banjarnegara dengan LSM GMTB di Sungai Gung Desa Kajen Kecamatan Lebaksiu Kabupaten Tegal ) - Tiara Lismawati; Suwanto Adhi; Puji Astuti (Journal of Politic and Government Studies, 2014)
This study was conducted to clarify the government's role in resolvingconflicts in the mining village of Galian C Kajen through the mediation process inthe case of conflict between PT BRD Banjarnegara with GMTB NGOs . It can beseen through how the cause and the beginning of the conflict, the beginning of themediation process does and the steps taken by the government in carrying out itsrole through the mediation process , as well as the end result of a process ofmediation .This study used qualitative research methods , in which the researcherscollected data written and spoken words of the research subjects and informants .Field data obtained by conducting in-depth interviews and the literature.These results indicate that the role of government through the mediationprocess is quite helpful in conflict resolution . After the mediation process is done, the conflict is reduced . Although it is said in the mediation process does notsucceed in the absence of the parties signed a document that outlines severaldispute resolution requirements . Yet when the Governor of Central Java BibitWaluyo allow mining by PT BRD , also requested that the district governmentand parliament make arrangements so that the miners do not harm theenvironment . Subsequent to the mediation , the case has not been completed todate . Of the GMTB NGOs not accept alternative provided by the mediator finallyreported the matter to the President of Indonesia Susilo Bambang Yudhoyono .The most dominant factor being the cause of the conflict is limited resources ,jurisdictional ambiguity , communication is not good and needs .